The Effect of Varicocelectomy on Semen Analysis and Serum Levels of InhibinB - Fallah, Mohammadreza Mohammadi; Tayyebi Azar, Ali (Archives of Men's Health, 2019)
Background: Varicocele means dilation and torsion of spermatic veins. About 15%-40% of infertile men suffer from Varicocele. It seems that 70% of secondary infertility in men occurs due to Varicocele. Varicocele is the most common surgical cause for male infertility. Varicocelectomy is considered as the best treatment method for patients with Varicocele that increases 30%-50% of the postoperative fertility rate. The purpose of this study was to investigate the effect of Varicocelectomy on inhibin B and use this marker to predict infertility in men. Methods: In this study, all infertile patients in any age that were candidate for Varicocelectomy and hospitalized in Imam Hospital in Urmia were included. Exclusion criteria were defined as orchitis, trauma, diabetes, radiotherapy, chemotherapy and coitus complications. Sperm analysis (SA) was conducted three times for patients and then serum levels of FSH, LH, T, inhibin B, SA were measured before surgery and also six months after surgery. Furthermore, during the hospitalization and infertility period, testes were examined before surgery in terms of consistency and size. Results: The mean ± SEM (standard error median) age of 40 patients was 28.4±5.14 (range: 18-40) years old. Mean size of the testes and mean sperm density and serum levels of LH.FSH remained the same. However, mean sperm motility, serum levels of T and inhibin B were statistically significant after the Varicocelectomy (p-value=0.005). A significant relationship was found between serum levels of inhibin B and infertility; however, there was no significant relationship between sperm count and serum levels of LH, FSH and T. Varicocelectomy can improve sperm motility and increase Inhibin B in patients and so improves spermatogenesis parameters and it may be one of the causes of fertility in patients. Conclusion: The results of this study indicate that sperm motility and increase in inhibin B after Varicocelectomy can improve spermatogenesis parameters. Serum levels of FSH, T, LH and sperm morphology and also grade of Varicocele, patient age, and testis size have no effect on spermatogenesis and fertility after Varicocelectomy.